The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1074/jbc.m107207200
|View full text |Cite
|
Sign up to set email alerts
|

The Rpb9 Subunit of RNA Polymerase II Binds Transcription Factor TFIIE and Interferes with the SAGA and Elongator Histone Acetyltransferases

Abstract: Rpb9 is a small subunit of yeast RNA polymerase II participating in elongation and formed of two conserved zinc domains. rpb9 mutants are viable, with a strong sensitivity to nucleotide-depleting drugs. Deleting the C-terminal domain down to the first 57 amino acids has no detectable growth defect. Thus, the critical part of Rpb9 is limited to a N-terminal half that contacts the lobe of the second largest subunit (Rpb2) and forms a ␤-addition motif with the "jaw" of the largest subunit (Rpb1). Rpb9 has homolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 51 publications
6
49
0
Order By: Relevance
“…This raises the possibility that TAF9-interacting genes for regulators of transcription elongation mostly represent SAGA-specific interactions, while those for Mediator and most chromatin modification/remodeling complexes largely represent TFIID-specific interactions. Supporting this notion, several studies are consistent with a role of SAGA in elongation (Van Mullem et al 2002;Rodriguez-Navarro et al 2004;Wery et al 2004), including the fact that SAGA physically and functionally interacts with both the transcription elongation factor TFIIS (Wery et al 2004) and the PolII subunit Rpb9, which has been linked to elongation control (Van Mullem et al 2002). Hence, to further examine possible involvement of SAGA in transcriptional elongation, we used ChIP to analyze the integrity of nucleosomes within the coding sequence of a gene known to be controlled by SAGA, PDR5 (Gao et al 2004).…”
Section: Caf40 Cdc40 Loc1supporting
confidence: 71%
“…This raises the possibility that TAF9-interacting genes for regulators of transcription elongation mostly represent SAGA-specific interactions, while those for Mediator and most chromatin modification/remodeling complexes largely represent TFIID-specific interactions. Supporting this notion, several studies are consistent with a role of SAGA in elongation (Van Mullem et al 2002;Rodriguez-Navarro et al 2004;Wery et al 2004), including the fact that SAGA physically and functionally interacts with both the transcription elongation factor TFIIS (Wery et al 2004) and the PolII subunit Rpb9, which has been linked to elongation control (Van Mullem et al 2002). Hence, to further examine possible involvement of SAGA in transcriptional elongation, we used ChIP to analyze the integrity of nucleosomes within the coding sequence of a gene known to be controlled by SAGA, PDR5 (Gao et al 2004).…”
Section: Caf40 Cdc40 Loc1supporting
confidence: 71%
“…In addition to its TCR function, Rpb9 has multiple transcription-related functions, such as selection of correct transcription start site (8,15,58), transcription elongation (12,49), and maintenance of transcription fidelity (29). In this paper, we present evidence that Rpb9 also plays an important role in Rpb1 ubiquitylation and degradation in response to UV radiation.…”
mentioning
confidence: 67%
“…5A) (5). The Zn1 and linker domains are required for transcription elongation (22,49) and TCR functions (22), whereas the entire Zn2 domain is dispensable for these functions in vivo. However, both Zn1 and Zn2 seem to play important roles in the selection of correct transcription start sites (8,15,43).…”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that the underlying biochemical basis for the alterations in the positions of mRNA 5Ј-ends conferred by the ⌬Rpb9 RNAPII involves an altered interaction involving the mutant polymerase and one or more of the purified general transcription factors in the reconstituted reactions. In this regard, it was recently reported that a GAL4-Rpb9 fusion protein, which contained the GAL4 DNA binding domain fused to a truncated Rpb9 lacking the N-terminal 32 amino acids, interacted with the large subunit of yeast TFIIE (Tfa1) in a yeast two-hybrid assay (28). Although this result suggests that Rpb9 might physically interact with TFIIE, the detected interaction in the two-hybrid assay was reported to be very weak with a GAL4-Rpb9 fusion protein containing the entire Rpb9 coding sequence.…”
Section: Fig 4 Rnapii Lacking the Rpb9 Subunit Is Impaired For Formmentioning
confidence: 99%